Internal and external financing of innovation: Sectoral differences in a longitudinal study of European firms. Issue 2 (10th May 2019) - Nylund, Petra A.; Arimany-Serrat, Nuria; Ferras-Hernandez, Xavier; Viardot, Eric; Boateng, Henry; Brem, Alexander
Abstract : Purpose: Successful innovation requires a significant financial commitment. Therefore, the purpose of this paper is to investigate the relation between internal and external financing and the degree of innovation in European firms. Design/methodology/approach: An empirical investigation is carried out using a longitudinal data set including 146 large, quoted, European firms over ten years, resulting in 1, 460 firm years. Findings: The authors find that only firms in the energy sector will be more innovative when they are profitable. For the sectors of basic materials, manufacture and construction, services, financial and property services, and technology and telecommunications, profitability is negatively related to innovation. External financing in the form of debt reduces the focus on innovation in profitable firms. Research limitations/implications: The authors analyze the findings through the lens of evolutionary economics. The model is not valid for firms in the consumer-goods sector, which indicates a need for adapting the model to each sector. We conclude that the impact of profitability on innovation varies across sectors, with debt financing as a moderating factor. Originality/value: To the best of authors' knowledge, this is the first study that analyzes the internal and external financing and the degree of innovation in European firms on a longitudinal basis.